PENINGKATAN KUALITAS LAYANAN PERPUSTAKAAN - Darmiyati Zuchdi (Universitas Negeri Yogyakarta, 1999)
Abstract This study was the broadening of a previous action research. The purpose of this study was to increase the interest of the students to read literature. This study was also aimed to explore the appropriateness of the literature for the students, the type of the assignment given by the lecturer, and the quality of circulation of the literature. This action research was done in nineteen undergraduate and one graduate courses from different study programs. The respondents of the study were the students and the lecturers of the courses. The data were collected using questionnaire and observation. The questionnaire was used to collect data from lecturers and from the students of the courses, while the observation was used to collect data about the activity of the students and the librarians. The data collected were analyzed quantatively, to describe of the percentage the respondents responding every question. The result of this study indicated that the majority of the students read the literature 1.5 hours per day outside the examination period and 3.5 hours during the examination period. The special service provided by IKIP Yogyakarta library combined with a systematic assignment from the lecturer made it possible for the students to be interested in reading the literature. This can be seen from the responses of the students, who generally viewed that most of the literatures were interesting, relevant, and very useful for the students to deepen their knowledge and skills. However, there were many of the students who found difficulties in understanding literature in English. The types of assignment given to the students were writing a book or report of reading, doing a discussion related to the literature, or writing a research proposal. The way the librarian handles the literature circulation was good. The condition of the reading room needed to be improved in order to be more comfortable. However that condition was better than the condition in the previous study. Keywords: reading interest, library service, and reserve literature.